The effect of naloxone on reproductive behavior and plasma prolactin levels after weaning in third lactation sows - Fuentes Hernández, Víctor Octavio; Bernal Canseco, Adriana; Fuentes Castro, Minerva Lidia; Orozco Hernández, José Rogelio (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
The present study was undertaken to study the effect of small doses of naloxone on behavior, prolactin plasma levels, interval of weaning to first estrus, and duration of estrus in third lactation sows. Thirty York x Landrace sows weaned at 25 to 27 days postpartum were selected and separated at random in two groups of 15. One group served as control and the other received every twelve hours two mg of naloxone im. Treatment with small doses of naloxone started three days before and continued for three days after weaning similarly the control group was injected with two mL of a saline solution. Naloxone treated sows showed estrus 88.8 Ó 6.2 hours after weaning (P